IS TEACHING JOB HARMONIOUS ANYMORE? A PRAGMATIC APPROACH TO WORK LIFE BALANCE OF YOUNG COLLEGE TEACHERS USING SEM - Dr. Praveen Paul J., Silambarasan M. (International Journal of Advanced Science and Technology, 2020)
A Teacher’s job has become multifaceted today. They no longer just focus on teaching but are forced to do many other clerical jobs which may not be related to their core job. Young college teachers are unable to fulfill their job requirements within the stipulated working hours and they find there is a spill over of these jobs into their personal life too. Thus they find it difficult to maintain a healthy balance between their professional life and personal life. Although work life balance (WLB) finds extensive attention in literature in India, there are no studies pertaining to WLB of young college teachers. This study focuses on young college teachers because they form the core future knowledge bearers of the country. If competent young teachers are not retained, then the educational institutions will be left with either non-competent or passionless teachers, who will jeopardize the future of students and the country. This study seeks to explore the impact of WLB and related factors on the turnover intention of young college teachers in India. For this study, college teachers from educational institutions spread over 17 states of India were considered. Findings of the study show that the teachers experience low work life balance high burnout and have high turnover intention.